FGF‐2 promotes initial osseointegration and enhances stability of implants with low primary stability. Issue 3 (26th February 2016) - Nagayasu‐Tanaka, Toshie; Nozaki, Takenori; Miki, Koji; Sawada, Keigo; Kitamura, Masahiro; Murakami, Shinya
Abstract: Objectives: The aim of this study was to examine the effect of basic fibroblast growth factor (FGF‐2) on osseointegration of dental implants with low primary stability in a beagle dog model. Materials and methods: Customized titanium implants that were designed to have low contact with the existing bone were installed into the edentulous mandible of beagle dogs. To degrade the primary stability of the implants, the diameters of the bone sockets exceeded the implant diameters. FGF‐2 (0.3%) plus vehicle (hydroxypropyl cellulose) or vehicle alone was topically applied to the sockets in the FGF‐2 and control groups, respectively. In Study 1, the new bone area and length of new bone‐to‐implant contact (BIC) were evaluated at 4, 8, and 12 weeks after installation using histomorphometry and scanning electron microscopy. In Study 2, the implant stability quotient (ISQ) values were sequentially measured for 16 weeks using an Osstell system. Results: The histomorphometric analysis revealed that the new bone area and length of BIC in the FGF‐2 group were significantly larger than those in the control group at 4 weeks. Electron microscopic observation showed intimate contact between the mature lamellar bone and the implant surfaces, osseointegration, in both groups. The ISQ values in the FGF‐2 group were significantly increased from 6 to 16 weeks compared with those in the control group. Conclusions: Taken together, our study demonstrates that FGF‐2 promoted new bone formation around the dental implants and subsequent osseointegration, resulting in promotion of stability of implants with low primary stability.